Expanded Field Theory New Axioms, Laws and Consequences (Global Journal of Science Frontier Research, 2022)
The present study attempts to expand the Classic Field Theory to a more general theory of the field This more general field theory is named Expanded Field Theory This new theory contains 2 new axioms and 8 laws It predicts to include the gravitational field and other unknown and unexplored fields As it is well known the Classic Field Theory is described mostly by Theory of Electromagnetic Field The Electromagnetic Field is described by Maxwell s laws 1864 The Maxwell s laws are certified by a single axiom which claims that the movement of a vector E in a closed loop div rot E 0 is evenly or velocity is constant